Faktor-Faktor yang Mempengaruhi Pendapatan Pedagang Kaki Lima Tahun 2020 (Studi Kasus: Pasar Gembong Asih Surabaya) - Sahid, Reza Achmad; Prayitno, Budi; Yustie, Renta (Economie: Jurnal Ilmu Ekonomi, 2022)
This study entitled "Factors Affecting Street Vendors in 2020 (Case Study: Pasar Gembong Asih Surabaya)" aims to determine how the influence of labor, working hours, labor wages on the income of traders. This research method uses multiple linear analysis with cross section data. The population in this study was 200 traders, the number of samples used was 40 traders. The results of the simultaneous multiple linear analysis of labor, working hours and labor wages together affect the income of traders. Partially, labor and working hours have no effect on the income of traders, while the wages of labor have an effect on the income of street vendors.